Breast cancer and incident cardiovascular events: A systematic analysis at the nationwide level. (10th February 2022) - Gue, Ying X.; Bisson, Arnaud; Bodin, Alexandre; Herbert, Julien; Lip, Gregory Y. H.; Fauchier, Laurent
Abstract: Background: Breast cancer (BC) is one of the most common cancers worldwide, and the treatments are frequently cardiotoxic. Whether BC is associated with a higher risk of cardiovascular events is a matter of debate. We evaluated the associations among BC and incident cardiovascular events in a contemporary population. Methods: All female patients discharged from French hospitals in 2013 with at least 5 years of follow‐up and without a history of major adverse cardiovascular event (myocardial infarction [MI], heart failure [HF], ischaemic stroke or all‐cause death, and MACE‐HF, which includes cardiovascular death, MI, ischaemic stroke or HF) or cancer (except BC) were identified. After propensity score matching, patients with BC were matched 1:1 with patients with no BC. Hazard ratios (HRs) for cardiovascular events during follow‐up were adjusted on age, sex and smoking status at baseline. Results: 1, 795, 759 patients were included, among whom 64, 480 (4.3%) had history of BC. During a mean follow‐up of 5.1 years, matched female patients with BC had a higher risk of all‐cause death (HR 3.55, 95% confidence interval [CI]: 3.47–3.64), new‐onset HF (HR 1.08, 95% CI 1.04–1.11), major bleeding (HR 1.43, 95% CI 1.36–1.49), MACE‐HF (HR 1.07, 95% CI 1.04–1.11) and net adverse clinical events (NACE) including all‐cause death, MI, ischaemic stroke, HF or major bleeding (HR 2.53, 95% CI 2.48–2.58) compared with those with no BC. By contrast, risks were not higher for cardiovascular death (HR 0.94, 95% CI 0.88–1.00) and were lower for MI (HR 0.81, 95% CI 0.75–0.88) and ischaemic stroke (HR 0.85, 95% CI 0.79–1.11). Conclusions: In a large and contemporary analysis of female patients seen in French hospitals, women with history of breast cancer had a higher risk of all‐cause mortality, new‐onset heart failure and major bleeding compared to a matched cohort of women without breast cancer. In contrast, they have a reduced risk of cardiovascular mortality, MI and stroke.